2001
DOI: 10.5860/crl.62.4.317
|View full text |Cite
|
Sign up to set email alerts
|

What Do They Really Think? Assessing Student and Faculty Perspectives of a Web-based Tutorial to Library Research

Abstract: Over the past thirty years, libraries have increasingly used forms of computer-assisted instruction (CAI) in place of librarians for basic instruction tasks. This study evaluates student and faculty perceptions of the Highlander Guide, a Web-based tutorial to library research. Overall, students (particularly those required to use it) and faculty reported positive views of the guide. Correlations drawn between student confidence in using the Web or conducting library research revealed that confident students re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Although preference for the tutorial over traditional instruction was not as strong as predicted, 53 percent of students "would recommend to other students" and 50.4 percent "prefer to formal instruction session." 10 Michel's study differs from others in that Radford's tutorial was an optional supplement to standard library instruction. The one section required to use the tutorial rated it more highly than did the overall test group.…”
mentioning
confidence: 92%
“…Although preference for the tutorial over traditional instruction was not as strong as predicted, 53 percent of students "would recommend to other students" and 50.4 percent "prefer to formal instruction session." 10 Michel's study differs from others in that Radford's tutorial was an optional supplement to standard library instruction. The one section required to use the tutorial rated it more highly than did the overall test group.…”
mentioning
confidence: 92%
“…7 In fact, Stephanie Michel specifically stated in her article that "the CAI (computer-assisted instruction) phenomenon resulted from libraries' inability to keep up with the tremendous demand for instruction." 8 This was true at IUPUI, and in order to address the problem, the library's team of instructional librarians investigated the possibility of developing a Web-based tutorial to alleviate these demands. The workgroup assigned to this task reported that time and resources needed for the development of such a tutorial precluded rapid development and that other venues should be explored.…”
Section: May 2004mentioning
confidence: 99%
“…5 Stephanie Michel also states that this type of instruction o en excludes students who are unfamiliar with or not comfortable utilizing computers or might have slower operating systems in their homes, where the computer-assisted instruction is more likely to be used.…”
Section: Literature Reviewmentioning
confidence: 99%